Pelagic population dynamics of Aurelia sp in French Mediterranean lagoons - Marques, Raquel (2018)
The pelagic dynamics of the cosmopolitan scyphozoan Aurelia sp. was investigated in three French Mediterranean lagoons, Thau, Berre and Bages-Sigean, which harbour resident populations. The annual cycles showed a common univoltine pattern in all lagoons where the presence of pelagic stages in the water column lasted similar to 8 months. Field observations showed a release of ephyrae in winter time followed by pronounced growth between April and July, when individuals reached the largest sizes, before disappearing from the water column. Maximum abundance of ephyrae and medusae were registered in Thau. Medusae abundance attained a maximum of 331 ind 100 m(-3) in Thau, 18 ind 100 m(-3) in Berre and 7 ind 100 m(-3) in Bages-Sigean lagoons. Temperature and zooplankton abundance appeared as leading factors of growth, where Bages-Sigean showed the population with higher growth rates (2.66 mm day(-1)) and maximum size (32 cm), followed by Thau (0.57-2.56 mm day(-1); 22.4 cm) and Berre (1.57-2.22 mm day(-1); 17 cm). The quantification of environmental windows used by the species showed wider ranges than previously reported in the Mediterranean Sea, which suggests a wide ecological plasticity of Aurelia spp. populations in north-western Mediterranean lagoons.